2019
DOI: 10.1111/jpn.13230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low‐protein diet supplementation with alpha‐ketoglutarate on growth performance, nitrogen metabolism and mTOR signalling pathway of skeletal muscle in piglets

Abstract: Excessive protein levels in diets result in incomplete digestion of nitrogenous nutrients that are excreted from the body, causing environment pollution. Alpha‐ketoglutarate (AKG) has been reported to decrease dietary protein levels, promote intestinal health in piglets and reduce environmental pollution. However, the underlying mechanisms of AKG are largely unknown. The objective of this study was to determine the effects of low‐protein diet supplementation of AKG on the growth performance, nitrogen metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
7
0
2
Order By: Relevance
“…The research showed that adding crystalline AA to diets could improve the digestible energy, metabolizable energy and net energy of growing pigs [21]. Similarly, adding crystalline AA to low-protein diets can improve performance and carcass traits of late-breeding sows [16]. Other studies have shown that adding branched chain AA to low-protein diets can improve the growth performance in pigs to a level similar to that of adequate protein diets [22].…”
Section: Aa Digestibilitymentioning
confidence: 97%
See 2 more Smart Citations
“…The research showed that adding crystalline AA to diets could improve the digestible energy, metabolizable energy and net energy of growing pigs [21]. Similarly, adding crystalline AA to low-protein diets can improve performance and carcass traits of late-breeding sows [16]. Other studies have shown that adding branched chain AA to low-protein diets can improve the growth performance in pigs to a level similar to that of adequate protein diets [22].…”
Section: Aa Digestibilitymentioning
confidence: 97%
“…All results were expressed as mean ± standard error of mean (SEM). All data were subjected to a one-way analysis of variance using the general linear model (GLM) procedure of SAS 8.2 statistical software (SAS Institute, Inc. Cary, NC, USA) [16] according to a completely randomized one-factorial design. Differences among experimental groups were identified via the Student-Newman-Keuls (SNK) test.…”
Section: Data Treatment and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pig products are a significant source of environmental nitrogen pollution [14]. In feeding management, controlled reduction of protein feed to reduce total protein levels in the ration and addition of synthetic forms of amino acids to meet their needs has become an effective way to reduce nitrogen emissions [15]. This manipulation to reduce ammonia emissions appears to be a highly effective and efficient method in pig farming [16; 17].…”
Section: Resultsmentioning
confidence: 99%
“…AKG has a great effect on promoting the absorption and metabolism of amino acids. The addition of AKG could enhance energy status and muscle mass by activating mechanistic target of rapamycin (mTOR) signaling pathway in piglets ( 10 ). Previous studies have also demonstrated that dietary AKG supplementation improved the growth performance and protein deposition of juvenile hybrid sturgeon ( Acipenser schrenckiif × A.baeriio ) ( 11 ).…”
Section: Introductionmentioning
confidence: 99%